Estudo da apoptose em pacientes infectados por Helicobacter Pylori portadores de doenças com diferentes riscos de desenvolvimento de câncer gástrico - Christiane Teixeira Cartelle (2010)
Chronic infection of the gastric mucosa by H. pylori is the main cause of chronic gastritis (CG) also implicated in the pathogenesis of atrophy and intestinal metaplasia (IM). These conditions are considered risk for developing gastric cancer (AGC) and it is assumed that infection in childhood increases risk to gastric cancer, so comparative studies between children and adults are justified. The organism modify the turnover of gastric mucosal proliferation and inducing apoptosis. However, the mechanisms and pathways in proliferative and apoptotic processes is not well understood. Although studies showed relationship between gastric carcinogenesis and expression of nitric oxide synthase induced (iNOS) it is still unknown if there is a correlation between inflammation, apoptosis and activation of this enzyme in terms of risk for the malignant transformation associated with infection by H. Pylori. In this study we investigated the apoptotic pathways in gastritis, gastric mucosa of children and adults and correlated the intensity of inflammation, iNOS expression and apoptotic index in gastric mucosa in adult patients with GC and GCA. We used retrospective and prospective material of children and adults biopsied for clarification of dyspeptic symptoms. Negative and positive samples for H. pylori were classified according to the pathologies of interest (UD, GC, and GCA). We studied by immunohistochemistry and quantified by digital morphometry the pro and anti-apoptotic protein expression of intrinsic and extrinsic pathways of apoptosis, as well as iNOS protein and the apoptosis marker M30 CytoDeath expression. In children and adults the preferred route is intrinsic and an increased expression of pro-apoptotic proteins of the intrinsic pathway (Bax and Bak), in addition to compensatory expression of anti-apoptotic proteins (Bcl2 and Bclx). Furthermore, Bax and Bak expression was higher in GCA compared to other diagnoses confirming the hypothesis that apoptosis can be related to susceptibility to cancer in long-term presence of mucosal atrophy. The iNOS expression was higher in H.pylori-negative patients than in the positive ones. There was no difference in apoptotic indices between patients H. Pylori-positive or negative or statistical correlation between the apoptotic index and the iNOS expression in patients H.Pylori-positive. A correlation between apoptotic index and the intensity of inflammation in infected patients was observed for mild and moderate degrees of gastritis.